The Strategy of Achieving Flexibility in Materials and Configuration of Flexible Lithium‐Ion Batteries. Issue 12 (10th November 2021) - Song, Wanrong; Liu, Xing; Li, Ting-Ting; Wang, Yanting; Zhang, Xuefei; Lou, Ching-Wen; Lin, Jia-Horng
Abstract : In recent years, with the development of flexible intelligent wearable devices, flexible batteries have attracted widespread attention in energy storage systems. To satisfy the power supply as well as the integrity of flexibility for the flexible intelligent wearable devices, the development of batteries with both excellent electrochemical performance and wearable flexibility has attracted a lot attention. This review is focused on the discussion of how to realize battery flexibility from the perspective of flexible lithium‐ion batteries as one of the most ideal and promising flexible power sources. Also, the development of flexible lithium‐ion batteries in recent years and the methods to achieve the flexibility are reviewed from the aspects of battery materials and electrode structures, to provide new ideas for research about flexible lithium‐ion battery with a high energy density in the future. Abstract : This review is focused on the discussion of how to realize flexibility. Also, the development of flexible lithium‐ion batteries in recent years and the methods to achieve the flexibility are reviewed from the aspects of battery materials and electrode structures, to provide new ideas for research about flexible lithium‐ion batteries with a high energy density in the future.